Molecular systematics and biogeography of the genus Zizina (Lepidoptera: Lycaenidae) - Yago, Masaya; Hirai, Norio; Kondo, Mariko; Tanikawa, Tetsuo; Ishii, Minoru; Wang, Min; Williams, Mark; Ueshima, Rei (Zootaxa, 2008)
Butterflies of the genus Zizina are widely distributed in all zoogeographical regions except the New World (North and South America) and the northern part of Eurasia. We address some of the problems in regard to the taxonomy and biogeography of the genus. We inferred phylogenetic relationships for all four species in the current classification of this genus from the ND5 region of mtDNA. From our molecular analyses and morphological evidence, we concluded that this genus contains three species; Z. otis, Z. oxleyi and Z. emelina. The status of the latter species is revised, while Z. labradus and Z. antanossa, which were formerly treated as specifically distinct, are regarded as subspecies of Z. otis. Based on our analyses, we also employ phylogeography to discuss possible speciation events in the genus. Each of the three Zizina species appears to have branched from the common ancestor, with a divergence time estimated to be about 2.5 million years ago. The ancestors of Z. oxleyi and Z. emelina are postulated to have adapted to a temperate climate, diverged in the northern and southern hemispheres, and resulted in the extant species from New Zealand and East Asia, respectively. In contrast, the ancestor of Z. otis adapted mainly to tropical and subtropical zones, and the extant Z. otis dispersed into the Afrotropical, Oriental and Australian regions. Feeding adaptations in the larvae also might have had an effect on speciation within Zizina. In addition, our results indicated that there is a possibility that the distribution of the New Zealand Z. oxleyi was reduced in extent by the introduction of Z. otis, which immigrated recently from Australia or its surroundings.